1998
DOI: 10.1046/j.1365-2133.1998.02411.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long-term treatment with tacalcitol on the psoriatic epidermis. A flow cytometric analysis

Abstract: During the last decade, novel analogues of 1alpha,25-dihydroxy vitamin D3 have been developed for the treatment of psoriasis. Recently, the efficacy of short-term treatment with the novel derivative tacalcitol (1alpha,24-dihydroxy vitamin D3) has been documented. However, data on the long-term effect of tacalcitol on psoriatic skin are sparse. In this study, we assessed the cell characteristics of the psoriatic epidermis after treatment with tacalcitol for up to 24 weeks. We investigated how long-term treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…This is in contrast with studies which showed that tacalcitol affects keratinization to some extent [2,7,24]. However, most authors conclude that the effect of tacalcitol on differentiation is limited [4,6,8].…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…This is in contrast with studies which showed that tacalcitol affects keratinization to some extent [2,7,24]. However, most authors conclude that the effect of tacalcitol on differentiation is limited [4,6,8].…”
Section: Discussioncontrasting
confidence: 53%
“…Several in vitro and in vivo studies showed the effect of tacalcitol on epidermal proliferation and differentiation, and the effect on inflammatory processes in skin [2][3][4][5][6][7][8]. Especially the effect on epidermal proliferation has shown to be most substantial [2,6,7]. This finding strongly suggests that the antipsoriatic effect of tacalcitol may be mediated by the normalization of epidermal cell cycle kinetics.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Ki-67 (-) 48 [16],71 [23] 35 [29],44 [24],69 [20] 70 [19] 77 [22] 84 [27] K10 (+) 22 [30],11 [34] 22 [29], 66 [25] 100 [31] SG2M (-) 26 [34],33 [15],34 [30] 44 [25] 71 [31] K16 (-) 26 [16],60 [15] 83 [24] 47 [22] Involucrin (-) [34] 61 [31] 45 [30] 85 [34] All vitamin D 3 analogues had a clear inhibitory effect on neutrophils [16,19,20].…”
Section: Marker +/-Calcipotriol Tacalcitol Calcitriol Calcipotriol+ Hmentioning
confidence: 99%
“…As can be seen in Table 2, calcipotriol, tacalcitol and betamethasone have varying effects on the percentage of vimentin+ cells. A substantial reduction of vimentin+ cells is reached by clobetasol and the combinations of calcipotriol with a corticosteroid [25,[29][30][31]34].…”
Section: Mesenchymal Cellsmentioning
confidence: 99%